Specific and non‐specific immunity of piglets from sows fed diets containing specific fatty acids in field conditions. Issue 5 (26th November 2012) - Benzoni, G.; Foresti, F.; Archetti, I. L.; Coceva, G.; Guyonvarch, A.; Alborali, L.
Summary The transfer of passive immunity from sows to piglets is important and it is the first immune protection of the new born piglet. Improving sows immunity by adding immuno‐stimulating product in sows diet can positively affect colostrum composition and transfer of immune molecules to piglets. The aim of the current study is to evaluate the benefit of a different solution, made of specific fatty acids from marine origin that have been used in human medicine for decades, for sows and piglets. Two trials were conducted in commercial farm, involving 240 sows at different periods of the year. Sows were divided in a control group, without supplementation, and a test group, supplemented with the feed additive from the 90th day of gestation to weaning. Sows body condition, piglets viability and growth were recorded. Milk immunoglobulin content was measured, as well as Aujeszky antibodies in sows and piglets blood as marker of specific immunity, and blood bactericidal activity, complement activity and lysozyme as markers of non specific immunity. No effect of the product was observed on piglets zootechnical criteria and specific immunity parameters but significant improvement of piglet non specific immunity, was observed. No difference was observed neither in the piglets blood PRRSV and PCV2 antibodies and viruses nor in Aujeszky antibodies. Blood complement activity seems to be an accurate indicator of immuno‐stimulating additive efficiency. Giving alkyl‐glycerol fatty acids to sows in late gestation and lactation can improve the passive immunity transfer to piglets.